Empowerment, Wellbeing and Mindset of Female Ecotourism Entrepreneurs in North Cyprus - Ertaç, Mürüde (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
As a small island in the Mediterranean, Cyprus is striving to develop a sustainable tourism model. Despite the limited opportunities due to the ongoing political problems of the island, the number and activities of women ecotourism entrepreneurs in Northern Cyprus has shown inspiring growth over the last decade. This study examines the impacts of ecotourism initiatives on women’s gender roles, from the perspectives of women, who are influenced by the traditional lifestyles in a developing country, North Cyprus, stuck in a frozen conflict. It assesses the achievements and challenges women face in ecotourism and its impact on their empowerment and wellbeing and the effects of an incremental growth mindset. The empowerment of these women through tourism can lead to their flourishing - higher levels of wellbeing - that influences their commitment and further involvement in the sector. Both qualitative and quantitative research methods were conducted to compare the results. The quantitative research model was developed based on the Self-Determination Theory. Our sample included 200 women ecotourism entrepreneurs in rural areas of Northern Cyprus. Our results show that women who have growth mindsets, i.e. those that believe people’s characteristics such as abilities are not fixed, benefit more from an empowering environment and reach higher levels of flourishing. A qualitative methodology with a feminist research was adopted to collect detailed information from forty female ecotourism entrepreneurs. Valuable information about their experiences, beliefs and attitudes, from the perspective of these female entrepreneurs, was collected through semi-structured interviews. The qualitative results supported that these women experienced an increase in their perceived economic, social and psychological empowerment and in their levels of wellbeing. However, due to gender inequality and the frozen conflict situation of North Cyprus, it was found that women who have a high growth mindset felt lower levels of wellbeing than those with a fixed mindset. This was because women with a high growth mindset were more aware of the limitations imposed on them by gender inequality and the political situation pertaining to North Cyprus which caused them to be frustrated. The research concludes that although all female ecotourism entrepreneurs experienced more empowerment and wellbeing, those with a high incremental mindset were frustrated by external factors which circumscribed their activities. The results can guide policy makers and stakeholder organizations in their efforts to support rural development, microfinance opportunities and women’s empowerment and well-being. Keywords: Self Determination Theory, Psychological Empowerment, Flourishing, Women Entrepreneurship, Growth Mindset, Ecotourism

ÖZ: Akdeniz'de küçük bir ada olan Kıbrıs, sürdürülebilir bir turizm modeli geliştirmeyi hedeflemektedir. Adanın süregelen siyasi sorunları nedeniyle fırsatların sınırlı olmasına rağmen, Kuzey Kıbrıs'taki kadın ekoturizm girişimcilerinin sayısı ve faaliyetleri son on yılda ilham verici bir büyüme göstermiştir. Bu çalışma, ekoturizm girişimlerinin kadınların cinsiyet rolleri üzerindeki etkilerini, gelişmekte olan bir ülke olan Kuzey Kıbrıs'ta donmuş bir çatışmaya sıkışmış ve geleneksel yaşam tarzI etkis altında olan kadınların bakış açısından incelemektedir. Kadınların ekoturizmde karşılaştıkları başarıları ve zorlukları, güçlenmeleri ve refahları üzerindeki etkilerini ve gelişime açık zihniyetin etkilerini değerlendirir. Turizm sektöründe girişimci kadınların güçlendirilmesi ve yetkinliklerinin geliştirilmesi, sektöre daha fazla dahil olmalarını sağlayacaktır. Kadın girişimcilerin güçlendirilmesi ülkemizin de daha yüksek gelişmişlik ve refah düzeylerine ulaşabilmesine yardımcı olacaktır. Araştırma modelimiz Kendi Kaderini Tayin Teorisi’ne (Self Determination Theory) dayanarak geliştirilmiştir. Örneklemimiz Kuzey Kıbrıs'ın kırsal bölgelerindeki 200 kadın ekoturizm girişimcisini içermektedir. Sonuçlarımıza göre, düşünce yapıları “gelişime” odaklı olan girişimci kadınlar - yani insanların yetenekleri ve diğer birçok özelliğinin sabit olmadığına inananlar – ve “sabit” düşünce yapısı olanlar insanların yetenekleri ve diğer birçok özelliğinin değişmediğine inananlara göre daha farklılık göstermektedir. “Gelişme” odaklı olanlar “Sabit” odaklı olanlara göre güçlendirici bir ortamdan daha fazla yararlanabilmektedir ve daha yüksek seviyelerde “iyi oluş düzeyine” (flourishing) ulaşmaktadır. Ayrıca, kırk kadın ekoturizm girişimcisinden ayrıntılı bilgi toplamak için feminist araştırmalarla nitel bir metodoloji benimsenmiştir. Bu kadın girişimcilerin bakış açısından deneyimleri, inançları ve tutumları hakkında değerli bilgiler yarı yapılandırılmış görüşmeler yoluyla toplanmıştır. Nitel sonuçlar, bu kadınların algılanan ekonomik, sosyal ve psikolojik güçlenmelerinde ve refah düzeylerinde bir artış yaşadıklarını desteklemiştir. Bununla birlikte, cinsiyet eşitsizliği ve Kuzey Kıbrıs'ın donmuş çatışma durumu nedeniyle, “gelişime açık” zihniyete sahip kadınların, “sabit zihniyete” sahip olanlardan daha düşük refah düzeyleri hissettikleri bulunmuştur. Bunun nedeni, “gelişime açık zihniyet” seviyesi yüksek kadınların cinsiyet eşitsizliği ve Kuzey Kıbrıs'la ilgili olarak hayal kırıklığına neden olan siyasi durumun getirdiği sınırlamaların daha fazla farkında olmalarıydı. Araştırma, tüm kadın ekoturizm girişimcilerinin daha fazla güçlendirme ve refah yaşamasına rağmen, “gelişme odaklı” bir zihniyete sahip olanların faaliyetlerini sınırlayan dış faktörlerden dolayı daha fazla hayal kırıklığına uğradığı sonucuna varmaktadır. Araştırma bulguları hem hükümetlere hem de sivil toplum örgütlerine ekoturizm ve kırsal kalkınmanın desteklenmesinde dikkat edilmesi gereken önemli unsurlar konusunda yol gösterici olabilecektir. Anahtar Kelimeler: Kendi Kaderini Tayin Teorisi, Psikolojik Güçlendirme, Gelişme, Kadın Girişimciliği, Gelişme ve Sabit Odaklı Düşünce Yapısı, Ekoturizm
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Co-Supervisor: Assoc. Prof. Dr. İlkay Yorgancı Maloney, Supervisor: Prof. Dr. Cem Tanova.
Keywords: Tourism; Entrepreneurship--Self-employed women--Tourism Sector--Ecotourism Initiatives--Women's Gender Roles--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Tourism--Entrepreneurship--Ecotourism--Sustainable tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Ecotourism--Nature conservation--Cyprus, North; Tourism--Businesswomen--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Women-owned business enterprises--Entrepreneurs--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Gender identity--Tourism Sector; Self Determination Theory; Psychological Empowerment; Flourishing; Women Entrepreneurship; Growth Mindset; Ecotourism